DEVELOPMENT OF STUDENT ASSESSMENT INSTRUMENTS FOR CIVIVCS LEARNING IN SMP/MTs - Leksono, Tangguh Timbul; Rarasati, Ida Putri (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2023)
This study focuses on creating a valid and practical assessment instrument for 8th-grade Civics Education (PPKn) students in junior high schools (SMP/MTs). The research employs the Research and Development (R&D) approach, adapting the Borg & Gall model by Sugiyono. The instrument, centered on Pancasila as the foundational principle of the state and national outlook, consists of 20 multiple-choice questions derived from a well-designed question matrix and indicators. Expert validation results show high approval scores for material and language aspects from two validators. The average validation score is 82.06%, affirming the instrument's validity. Educator and student questionnaire responses demonstrate strong practicality support, with average response rates of 83.89% and 87.60%, respectively. Analysis of the 20 questions confirms 18 valid questions, 2 needing revision, establishing the instrument's reliability (reliability coefficient r11 = 0.819). Difficulty analysis reveals 16 easy and 4 moderately difficult questions. Discrimination power assessment indicates 9 adequately differentiating and 11 highly discriminative questions. The study confirms the successful development of a valid and practical assessment tool for enhancing Civics Education in junior high schools, rejecting the null hypothesis.